Textual criticism of the Hebrew Bible, Qumran, Septuagint : collected essays - Tov, Emanuel. (Vetus Testamentum, Supplements, 2015)
Thirty-three revised and updated essays on the textual criticism of the Hebrew Bible, Qumran and the Septuagint, originally published between 2008 and 2014 are presented in this volume, the third volume of the author's collected writings. All three areas have developed much in modern research, and the auhor, the past editor-in-chief of the international Dead Sea Scrolls publication project, is a major speaker in all of them. The scrolls are of central importance in the modern textual research and this aspect is well represented in this volume. Among the studies included in this volume are central studies on coincidence, consistency, the Torah, the nature of the MT and SP, the diffusion of manuscripts, and the LXX of Genesis. The previous two volumes are: The Greek and Hebrew Bible: Collected Essays on the Septuagint (VTS 72; Leiden: Brill, 1999). Hebrew Bible, Greek Bible, and Qumran: Collected Essays (TSAJ 121; Tübingen: Mohr Siebeck, 2008).